Comparable Psychotropic Prescription Rates After Hospital Discharge Between Patients with COVID-19 and Those With Non-COVID-19-Related Respiratory Infection - Takahashi, Yuna; Yatomi, Taisuke; Yamaguchi, Naohito; Yoshimura, Kimio; Hori, Satoko; Uchida, Hiroyuki (Pharmacopsychiatry, 2024)
Introduction Whether psychiatric symptoms after recovery from coronavirus disease 2019 (COVID-19) are specific to this illness remains unclear.Methods In this retrospective study, the Diagnosis Procedure Combination data and outpatient clinic data were used for patients who received inpatient treatment in Saiseikai-affiliated hospitals for COVID-19 or other respiratory tract infections (non-COVID) from 2020 to 2022. The primary outcome was new prescriptions of psychotropic drugs after discharge (i. e., prescriptions of psychotropics to patients who had not received them before or during their hospitalization). Values of interest were compared between groups using the chi-square test or Fisher’s exact test. A COX proportional-hazards model was used to examine factors associated with psychotropic prescriptions after discharge in age- and sex-matched COVID-19 and non-COVID patients.Results Of 31,993 chart records, 19,613 were excluded due to a positive history with psychiatric disorders (n=2,445), prescriptions of psychotropics (n=744), and no follow-ups (n=16,424). Thus, 3,648 COVID-19 and 8,732 non-COVID patients were included (mean [range] duration of follow-up, days: 146.9 [1–727] and 239.2 [1–729], respectively). Two hundred and four (5.6%) of the 3,648 patients with COVID-19 received psychotropic prescriptions after discharge. No statistically significant differences were observed in the prescription rates of any psychotropic category between the COVID-19 and non-COVID groups. An increase in severity during hospitalization was significantly associated with more frequent psychotropic prescriptions (hazard ratio 1.83, p<0.001).Discussion The development of psychiatric symptoms should be closely observed, especially in patients who experienced increased severity during hospitalization, regardless of whether they suffered from COVID-19.
Keywords: coronavirus disease 2019; COVID-19; hypnotics; psychotropics